2020
DOI: 10.1155/2020/4586875
|View full text |Cite
|
Sign up to set email alerts
|

A Stacking Ensemble for Network Intrusion Detection Using Heterogeneous Datasets

Abstract: The problem of network intrusion detection poses innumerable challenges to the research community, industry, and commercial sectors. Moreover, the persistent attacks occurring on the cyber-threat landscape compel researchers to devise robust approaches in order to address the recurring problem. Given the presence of massive network traffic, conventional machine learning algorithms when applied in the field of network intrusion detection are quite ineffective. Instead, a hybrid multimodel solution when sought i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(70 citation statements)
references
References 37 publications
0
70
0
Order By: Relevance
“…The varying gene expression can be efficiently analyzed using microarray where all the genes of a particular organism are placed in different grooves on a slide. Gene expression data could be effectively maintained and processed using statistical methods to analyze diseases much easier [14]. The state of a cell communicated by the layout of RNA will thusly serve to be of great help to check whether a cell might be a normal or a variation one [15].…”
Section: Related Workmentioning
confidence: 99%
“…The varying gene expression can be efficiently analyzed using microarray where all the genes of a particular organism are placed in different grooves on a slide. Gene expression data could be effectively maintained and processed using statistical methods to analyze diseases much easier [14]. The state of a cell communicated by the layout of RNA will thusly serve to be of great help to check whether a cell might be a normal or a variation one [15].…”
Section: Related Workmentioning
confidence: 99%
“…The experiments revealed that fuzzy SVM is more robust than SVM. A predictive model using stacking for intrusion detection was developed 24 . The system was tested on UNSW‐NB15 and UGR'16 datasets and results show that misclassification rate is minimal.…”
Section: Related Workmentioning
confidence: 99%
“…To strengthen proposed scheme, we have also analyzed our framework with publically available TUIDS [19], UNSW-NB15 [20,22] and UNIBS datasets [21]. Figure 7 illustrates the impact of processing delay with respect to node density in presence of insider malicious adversaries.…”
Section: Figure6 Guiding Principle Implementation Framework Assessmentmentioning
confidence: 99%